The Moral Minefield of Ethical Oil Palm and Sustainable Development - Meijaard, Erik; Sheil, Douglas (Frontiers in Forests and Global Change, 2019)
The environmental impacts of the palm oil industry are widely recognised. Unsurprisingly, many people, including many conservation pundits, consider oil palm a major evil. What is less widely recognized is the extent to which this industry has benefited people. Oil palm development, if well-planned and managed, can provide improved incomes and employment and generate investments in services and infrastructure. These alternative viewpoints fuel a polarised debate in which oil palm is alternatively seen as a gift from god or a crime against humanity. Stepping outside this rhetorical extremism is necessary if we seek resolution and pragmatic advances. An important question is how to plan, guide and assess oil palm developments to foster the greatest benefits and least harm. Such questions are particularly relevant in a global context in which many voices call for constraining oil palm developments and boycotting palm oil, but also for adhering to sustainable development goals. What opportunities are available to people in tropical forest regions if oil palm developments are prohibited? Broader ethical questions also play out in the contexts of biofuels and food security and of competition among oil crops, especially the crops at higher latitudes (e.g., soy, maize, sunflower, rapeseed, olive), versus the tropical oils (oil palm and coconut). We here explore some of the questions of ethics related to the production and use of palm oil and other vegetable oils. The goal of this article is not to answer these contested questions but rather to highlight some of the nuances that are often omitted in current debates. Judgements will reflect perspectives with tropical producers and temperate consumers framing and assessing the issues differently. Addressing gaps in understanding on ethics of palm oil production, and avoiding double-standards, will help find a shared framework for development involving oil palm and other oil crops. A commitment to ethical consistency, where double standards are recognised and avoided, offers a potential way forward.